Encrypted Text Steganography in Audio Files Using ECC, LSB and Chaotic Maps - Jaafar, Abdullah; Abdullwale, Mayadah; Mohammed, Ahmed Abdulqader (مجـلـة جـامـعـة السـعيد للعلـوم التطبيقية, 2025)
Steganography ensures secure data transmission by concealing sensitive information within innocuous carrier files, such as audio, to evade detection. This paper proposes a robust steganographic framework that combines Elliptic Curve Cryptography (ECC) for encryption with Least Significant Bit (LSB)-based audio steganography, enhanced by chaotic maps to improve security and unpredictability. The methodology first encrypts the secret data using ECC, leveraging its high security with compact key sizes, and then embeds the ciphertext into audio files via dynamic LSB substitution, guided by chaotic sequences to randomize bit positions. Experimental evaluations demonstrate the scheme’s effectiveness in maintaining audio fidelity (assessed via PSNR and SNR metrics) while ensuring high embedding capacity and robustness against steganalysis. Security analysis confirms resilience to brute-force and entropy-based attacks due to the dual-layer protection of ECC and chaotic randomization. This study presents an innovative approach that comprehensively addresses the core steganographic requirements of imperceptibility, embedding capacity, and resistance to detection, thus providing a reliable framework for clandestine data transmission in security sensitive applications.